A microcrystalline glass and a microcrystalline glass substrate
Patent Information
- Application Number
- CN202311831908.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-06-04
- Filing Date
- 2016-05-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2036-05-31
AI Technical Summary
Existing microcrystalline glass has insufficient transmittance and color balance in protective components for portable electronic devices and optical equipment, and its low production efficiency makes it difficult to meet high strength requirements.
By controlling the composition ratio of glass-ceramics, especially the content and molar ratio of SiO2, Al2O3, Na2O, MgO, ZnO and TiO2, specific crystalline phases, such as RAl2O4, RTi2O5, R2TiO4, R2SiO4, and R2Al4Si5O18, are precipitated to form a compressive stress layer, thereby improving mechanical strength and light transmittance.
Microcrystalline glass achieves high transmittance and good color balance, with high strength and high Vickers hardness, making it suitable for protecting components and reducing production costs.
Smart Images

Figure BDA0004636570470000141 
Figure BDA0004636570470000151 
Figure BDA0004636570470000161
Abstract
Description
Technical Field
[0001] This invention relates to a microcrystalline glass and a substrate based on the microcrystalline glass. In particular, this invention relates to a microcrystalline glass and a substrate that have good visible light transmittance and color balance and high strength, suitable for protective components of portable electronic devices or optical devices. Background Technology
[0002] Protective glass is used to protect the displays of portable electronic devices such as smartphones and tablet PCs. Additionally, protective films are used to protect lenses in automotive optical equipment. The materials used for these protective glasses and films require high visible light transmittance, excellent color balance, and high strength. Furthermore, in recent years, to ensure these devices can withstand harsher environments, even stronger materials are required for protective glass and films.
[0003] Previously, chemically strengthened glass was used as the material for the protective components. However, conventional chemically strengthened glass is very brittle against cracks that penetrate vertically from the glass surface, which often leads to accidents where portable devices break when dropped, thus becoming a problem.
[0004] In addition, as a material with higher hardness than glass and transparency, sapphire has attracted much attention. However, in terms of manufacturing, sapphire has lower productivity and poorer machinability compared to glass.
[0005] In addition to the aforementioned materials, to improve the strength of glass, there is a type of glass-ceramic where crystals precipitate within the glass. Glass-ceramics can possess higher mechanical properties than amorphous glass, but conventional glass-ceramics are unsuitable for the aforementioned protective components due to poor visible light transmittance and color balance. Furthermore, conventional glass-ceramics suffer from low production rates due to the high viscosity or devitrification of their raw glass, making them difficult to use in the aforementioned protective components.
[0006] Patent Document 1 discloses a microcrystalline glass substrate for information recording media. This microcrystalline glass substrate has poor visible light transmittance and color balance. Furthermore, during chemical strengthening, sufficient compressive stress cannot be obtained, preventing the formation of a deep stress layer.
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2014-114200
[0008] The technical problem that the invention aims to solve
[0009] The present invention was made in view of the above-mentioned problems. The object of the present invention is to obtain a microcrystalline glass or substrate that is suitable for protective components of portable electronic devices and optical devices, has high visible light transmittance and good color balance, and also has high strength.
[0010] Furthermore, an objective of this invention is to obtain the aforementioned microcrystalline glass or substrate at a lower cost. Therefore, obtaining a microcrystalline glass with a low viscosity of the base glass and low devitrification is also one of the problems to be solved by this invention.
[0011] In order to solve the above-mentioned problems, the inventors of this invention, through repeated and in-depth experiments and research, solved the above-mentioned problems by specifying the content and proportion of specific components constituting the glass-ceramic to specific values and causing them to precipitate specific crystalline phases, thus completing this invention. Specifically, this invention provides a glass-ceramic or a glass-ceramic substrate with the following structure.
[0012] (Component 1)
[0013] A microcrystalline glass, characterized in that, calculated as a mole percent of oxides, it contains:
[0014] SiO2 composition 30.0% ~ 70.0%,
[0015] Al2O3 composition 8.0% ~ 25.0%,
[0016] Na2O composition 0% ~ 25.0%,
[0017] MgO content 0% ~ 25.0%,
[0018] ZnO content 0%–30.0%, and
[0019] TiO2 composition 0% ~ 10.0%,
[0020] The molar ratio [Al₂O₃ / (MgO+ZnO)] is between 0.5 and 2.0.
[0021] The crystal phases include RAl₂O₄, RTi₂O₅, R₂TiO₄, R₂SiO₄, RAl₂Si₂O₈, and R₂Al₄Si₅O. 18 One or more are selected from Zn, Mg, and Fe, where R is one or more selected from Zn, Mg, and Fe.
[0022] (Component 2)
[0023] According to the microcrystalline glass of composition 1, the characteristic is that, calculated in molar percentage of oxides, the molar ratio of TiO2 to Na2O [TiO2 / Na2O] is 0 or more and 0.41 or less.
[0024] (Component 3)
[0025] According to the microcrystalline glass of configuration 1 or configuration 2, the characteristic is that, calculated in molar percentage of oxides, the molar ratio of MgO to Na2O [MgO / Na2O] is 0 or more and 1.60 or less.
[0026] (Component 4)
[0027] The microcrystalline glass according to any one of configurations 1 to 3 is characterized in that the transmittance at a wavelength of 500 nm, including reflection loss, is more than 50% in a thickness of 1 mm.
[0028] (Component 5)
[0029] The microcrystalline glass according to any one of configurations 1 to 4 is characterized in that, in a thickness of 1 mm, the difference between the transmittance at wavelength 700 nm and the transmittance at wavelength 500 nm, including reflection loss, is within 2.0%, and the difference between the transmittance at wavelength 700 nm and the transmittance at wavelength 410 nm is within 6.0%.
[0030] (Composition 6)
[0031] The microcrystalline glass according to any one of constituents 1 to 5 is characterized in that, calculated in molar percentage of oxides, the total content of MgO and ZnO is 1.0% to 30.0%.
[0032] (Component 7)
[0033] The microcrystalline glass according to any one of constituents 1 to 6 is characterized in that, calculated in mole percent of oxides, it contains:
[0034] B2O3 content 0%–25.0%,
[0035] P2O5 composition 0%~10.0%,
[0036] K2O composition 0%~20.0%,
[0037] CaO content 0%–10.0%,
[0038] BaO content 0%–10.0%,
[0039] FeO component 0% ~ 8%,
[0040] ZrO2 composition 0% ~ 10.0%,
[0041] SnO2 content is 0% to 5.0%.
[0042] (Composition 8)
[0043] The microcrystalline glass according to any one of constituents 1 to 7 is characterized in that, calculated in mole percent of oxides, it contains:
[0044] Li2O composition 0% ~ 10.0%,
[0045] SrO composition 0% ~ 10.0%,
[0046] La2O3 content 0%–3%
[0047] Y2O3 content 0%–3%
[0048] Nb2O5 composition 0% ~ 5%,
[0049] Ta2O5 composition 0% ~ 5%,
[0050] WO3 component 0% to 5%.
[0051] (Composition 9)
[0052] A microcrystalline glass substrate, which uses the microcrystalline glass described in configurations 1 to 8 as a substrate and has a compressive stress layer on its surface, characterized in that the compressive stress value of the compressive stress layer is 300 MPa or more.
[0053] (Composition 10)
[0054] According to the microcrystalline glass substrate described in configuration 9, the thickness of the compressive stress layer is 1 μm or more.
[0055] Invention Effects
[0056] According to the present invention, a microcrystalline glass or substrate can be obtained, which is suitable for protective components of portable electronic devices and optical devices, and has high visible light transmittance, good color balance, and high strength. The microcrystalline glass of the present invention has a transmittance of more than 50% at a wavelength of 500 nm, including reflection loss, in a thickness of 1 mm; more preferably, more than 70%; and more preferably, more than 80%.
[0057] The microcrystalline glass of the present invention, including the transmittance at wavelength 700 nm and transmittance at wavelength 500 nm, has a transmittance difference ΔT1 within 2.0% and a transmittance difference ΔT2 between wavelength 700 nm and wavelength 410 nm within 1 mm thickness, including the reflection loss, within 6.0%. According to a more preferred embodiment, ΔT1 is within 1.5% and ΔT2 is within 5.0%. According to a more preferred embodiment, ΔT1 is within 1.2% and ΔT2 is within 2.5%.
[0058] Furthermore, the microcrystalline glass of the present invention has a Vickers hardness [Hv] of 600 or more, more preferably 650 or more, more preferably 700 or more, and more preferably 730 or more.
[0059] The microcrystalline glass of this invention, due to its high visible light transmittance, can also be used as a material for optical lenses. Furthermore, it can be used in other decorative applications such as the outer frame components of portable electronic devices that fully utilize the unique shape of glass materials. Detailed Implementation
[0060] The following describes in detail embodiments of the microcrystalline glass of the present invention. However, the present invention is not limited to these embodiments, and appropriate modifications can be made within the scope of the present invention. Furthermore, repeated parts in the description may sometimes be appropriately omitted, but this does not limit the spirit of the invention.
[0061] Microcrystalline glass, also known as glass-ceramic, is a material formed by precipitating crystals within glass through heat treatment. The microcrystalline glass of this invention is a material possessing both a crystalline phase and a glassy phase, distinguishing it from amorphous solids. Through internally dispersed crystallization, microcrystalline glass can possess physical properties unattainable in glass. For example, it can impart physical properties that are impossible to achieve in glass, such as Young's modulus, fracture toughness, and other mechanical strengths; etching characteristics against acidic or alkaline solutions; thermal properties such as the coefficient of thermal expansion; and the rise and fall of the glass transition temperature (improved heat resistance).
[0062] The crystal phase of glass-ceramics can be identified by the peak angles appearing in the X-ray diffraction pattern of X-ray diffraction analysis, and by using TEMEDX as needed.
[0063] The microcrystalline glass of the present invention contains, as a crystalline phase, RAl₂O₄, RTi₂O₅, R₂TiO₄, R₂SiO₄, RAl₂Si₂O₈, and R₂Al₄Si₅O. 18 (But R is selected from one or more of Zn, Mg, and Fe)
[0064] Microcrystalline glass with these crystal phases exhibits high mechanical strength even with very small crystal precipitation. Therefore, microcrystalline glass with these crystals as the crystalline phase has the high strength required for protective components in portable electronic devices and optical equipment, and also readily achieves high light transmittance and good color balance.
[0065] [Composition of glass-ceramic]
[0066] The composition range of each component constituting the microcrystalline glass of the present invention will be described below. In this specification, unless otherwise specified, the content of each component is expressed as mol% relative to the total amount of glass material converted to oxides. Here, "composition converted to oxides" means that, assuming that all oxides, complex salts, metal fluorides, etc., used as raw materials for the microcrystalline glass of the present invention decompose and transform into oxides upon melting, the total amount of the generated oxides is taken as 100 mol%, indicating the composition of each component contained in the glass.
[0067] In addition, when referred to as glass in this specification, it sometimes includes uncrystallized glass.
[0068] SiO2 is an essential component for forming the glass network structure of the glass-ceramic of the present invention. If its content is less than 30%, the resulting glass has poor chemical durability and poor devitrification resistance. Therefore, the lower limit of the SiO2 content is preferably 30.0%, more preferably 40.0%, and most preferably 50.0%.
[0069] On the other hand, by keeping the SiO2 content below 70.0%, excessive viscosity increase and decreased meltability can be suppressed. Therefore, the upper limit of the SiO2 content is preferably 70.0%, more preferably 68.0%, more preferably 66.5%, and most preferably 65.0%.
[0070] Al2O3, like SiO2, is an essential component for forming the glass network structure and can also become a constituent of the crystalline phase through heat treatment of the raw glass. It is an important component that helps stabilize the raw glass and improve its chemical durability, but its effect is poor if its content is less than 8.0%. Therefore, the lower limit of the Al2O3 content is preferably 8.0%, more preferably 10.0%, and most preferably 12.0%.
[0071] On the other hand, if the Al2O3 content exceeds 25.0%, the meltability and devitrification resistance decrease. Therefore, the upper limit of the Al2O3 content is preferably 25.0%, more preferably 20.0%, more preferably 17.0%, and most preferably 15.0%.
[0072] Na2O is an optional component for improving low-temperature melting and formability.
[0073] On the other hand, by keeping the Na₂O content below 25.0%, the decrease in chemical durability or the increase in the average coefficient of linear expansion caused by excessive Na₂O content can be suppressed. Therefore, the upper limit of the Na₂O content is preferably 25.0%, more preferably 20.0%, and most preferably 15.0%.
[0074] During chemical strengthening via ion exchange, the microcrystalline glass contains Na₂O, thus increasing the amount of Na in the microcrystalline glass. + Ions and K + Ion exchange is highly effective in forming a compressive stress layer. Therefore, when chemically strengthening by ion exchange, the lower limit of the Na₂O content is preferably more than 0%, more preferably 2.0%, more preferably 4.0%, and most preferably 6.0%.
[0075] MgO is one of the components that can form a crystalline phase and is an optional component. When the content of MgO exceeds 0%, it has the effect of improving low-temperature melting properties. Therefore, the lower limit of the MgO content is preferably more than 0%, more preferably 3.0%, and even more preferably 5.0%.
[0076] On the other hand, by keeping the MgO content below 25.0%, the decrease in devitrification resistance caused by excessive MgO content can be suppressed. Therefore, the upper limit of the MgO content is preferably 25.0%, more preferably 20.0%, and most preferably 15.0%.
[0077] ZnO is one of the components that can form a crystalline phase and is an optional component. When the ZnO content exceeds 0%, it not only improves low-temperature melting properties but also enhances chemical durability. Therefore, the lower limit of the ZnO content is preferably more than 0%, more preferably 3.0%, more preferably 6.0%, and most preferably 8.0%.
[0078] On the other hand, by keeping the ZnO content below 30.0%, the reduction in devitrification can be suppressed. Therefore, the upper limit of the ZnO content is preferably 30.0%, more preferably 20.0%, more preferably 15.0%, and most preferably 10.0%.
[0079] TiO2 acts as a nucleation point for crystallization, and is an optional component that helps reduce the viscosity of glass-ceramics and improve chemical durability. The lower limit of the TiO2 content is preferably more than 0%, more preferably 0.5%, more preferably 1.0%, and most preferably 1.5%.
[0080] On the other hand, by keeping the TiO2 content below 10.0%, the reduction in devitrification can be suppressed. Therefore, the upper limit of the TiO2 content is preferably 10.0%, more preferably 7.0%, more preferably 4.0%, and most preferably 3.0%.
[0081] In this invention, to obtain the desired crystalline phase, it is necessary to ensure that the molar ratio of Al2O3 content to the total content of MgO and ZnO, i.e., the value of [Al2O3 / (MgO+ZnO)], is in the range of 0.5 to 2.0, calculated in molar percentages of oxides. To more easily achieve this effect, the lower limit of the value of [Al2O3 / (MgO+ZnO)] is preferably 0.6, more preferably 0.7, and most preferably 0.8. Similarly, the upper limit of the value of [Al2O3 / (MgO+ZnO)] is preferably 1.8, more preferably 1.5, and most preferably 1.2.
[0082] In this invention, to obtain the desired visible light transmittance and color balance, the molar ratio of TiO2 to Na2O, calculated in molar percentages of oxides, i.e., the value of [TiO2 / Na2O], is preferably in the range of 0 to 0.41. To more easily achieve the desired effect, the lower limit of the [TiO2 / Na2O] value is preferably 0.05, more preferably 0.10, and most preferably 0.12. Similarly, the upper limit of the [TiO2 / Na2O] value is preferably 0.41, more preferably 0.35, more preferably 0.25, and most preferably 0.15.
[0083] In this invention, although the resistance to devitrification, as well as the meltability and formability, are better during melting, strong coloring is suppressed. In order to obtain the desired microcrystalline glass with better color balance, the molar ratio of MgO to Na2O, i.e., the value of [MgO / Na2O], is preferably in the range of 0 to 1.60, calculated in molar percentage of oxides.
[0084] To more easily achieve the desired effect, the lower limit of the [MgO / Na2O] value is preferably 0.10, more preferably 0.30, and most preferably 0.50. Similarly, the upper limit of the [MgO / Na2O] value is preferably 1.60, more preferably 1.10, more preferably 0.80, and most preferably 0.60.
[0085] In this invention, to obtain the desired crystalline phase with better meltability and formability, the total content of MgO and ZnO components, i.e., the value of [MgO+ZnO], is preferably in the range of 1.0% to 30.0%, calculated as a mole percent of oxides. To more easily achieve this effect, the lower limit of the value of [MgO+ZnO] is preferably 5.0%, more preferably 10.0%, and most preferably 12.0%. Similarly, the upper limit of the value of [MgO+ZnO] is preferably 30.0%, more preferably 20.0%, more preferably 18.0%, and most preferably 16.0%.
[0086] In this invention, in order to obtain a microcrystalline glass that can precipitate very small crystals and has high light transmittance and good color balance, the molar ratio of ZnO to MgO, i.e., the value of [ZnO / MgO], is preferably in the range of 0 to 5, calculated in molar percentage of oxides.
[0087] To more easily achieve the desired effect, the lower limit of the [ZnO / MgO] value is more preferably 0.44, and most preferably 0.45. Similarly, the upper limit of the [ZnO / MgO] value is more preferably 4.8, and most preferably 4.7.
[0088] When the content of B2O3 exceeds 0%, it helps to reduce the viscosity of glass and improve its solubility and formability, so it can be added as an optional component.
[0089] On the other hand, if the B2O3 content is too high, the chemical durability of the glass-ceramic can easily decrease, and the desired crystallization can be easily inhibited. Therefore, the upper limit of the B2O3 content is preferably 25.0%, more preferably 10.0%, even more preferably 5.0%, and most preferably less than 2.0%.
[0090] P2O5 is an optional component that helps improve the low-temperature melting properties of glass when its content exceeds 0%.
[0091] On the other hand, excessive P2O5 content can easily lead to a decrease in devitrification resistance and phase separation in the glass. Therefore, the upper limit of P2O5 content is preferably 10.0%, more preferably 5.0%, and most preferably 1.0%.
[0092] K2O is an optional component that helps improve the low-temperature melting and formability of glass.
[0093] On the other hand, excessive K2O content can easily lead to a decrease in chemical durability and an increase in the average coefficient of linear expansion. Therefore, the upper limit of K2O content is preferably 20.0%, more preferably 10.0%, and most preferably 5.0%.
[0094] When chemically strengthening via ion exchange, the presence of K₂O in the glass-ceramic is highly effective in forming a deep compressive stress layer. Therefore, the lower limit of the K₂O content during chemical strengthening via ion exchange is preferably more than 0%, more preferably 0.5%, more preferably 0.8%, and most preferably 1.0%.
[0095] CaO is an optional component that helps improve the low-temperature melting properties of glass when its content exceeds 0%.
[0096] On the other hand, if the CaO content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the CaO content is preferably 10.0%, more preferably 5.0%, even more preferably 3.0%, and most preferably 1.0%.
[0097] BaO is an optional component that helps improve the low-temperature melting properties of glass when its content exceeds 0%.
[0098] On the other hand, if the BaO content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the BaO content is preferably 10.0%, more preferably 5.0%, more preferably 3.0%, and most preferably 1.0%.
[0099] FeO is one of the components that can form a crystalline phase, and since it can also function as a clarifying agent, it can be included arbitrarily.
[0100] On the other hand, if there is too much FeO, over-coloring or alloying of platinum in the glass melting apparatus can easily occur. Therefore, the upper limit of the FeO content is preferably 8.0%, more preferably 4.0%, and most preferably 1.0%.
[0101] ZrO2 can act as a nucleation point for crystallization and is also an optional component that helps improve the chemical durability of glass. Therefore, the lower limit of the ZrO2 content is preferably more than 0%, more preferably 0.4%, more preferably 0.8%, and most preferably 1.0%.
[0102] On the other hand, if the ZrO2 content is too high, the glass's devitrification resistance can easily decrease. Therefore, the upper limit of the ZrO2 content is preferably 10.0%, more preferably 4.0%, even more preferably 2.0%, and most preferably 1.5%.
[0103] SnO2 is an optional component that can function as a clarifying agent and to facilitate the formation of nuclei for crystallization. Therefore, the lower limit of the SnO2 content is preferably more than 0%, more preferably 0.01%, and most preferably 0.05%.
[0104] On the other hand, if the SnO2 content is too high, the glass's devitrification resistance can easily decrease. Therefore, the upper limit of the SnO2 content is preferably 5.0%, more preferably 1.0%, even more preferably 0.4%, and most preferably 0.2%.
[0105] Li₂O is an optional component for improving the low-temperature melting and formability of glass.
[0106] On the other hand, excessive Li₂O content can easily lead to a decrease in chemical durability or an increase in the average coefficient of linear expansion. Therefore, the upper limit of the Li₂O content is preferably 10.0%, more preferably 5.0%, and most preferably 2.0%.
[0107] When chemically strengthening via ion exchange, the presence of Li₂O in the glass-ceramic is highly effective in forming a deep compressive stress layer. Therefore, the lower limit of the Li₂O content during chemical strengthening via ion exchange is preferably more than 0%, more preferably 0.5%, more preferably 0.8%, and most preferably 1.0%.
[0108] SrO is an optional component that improves the low-temperature melting properties of glass when its content exceeds 0%.
[0109] On the other hand, if the SrO content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the SrO content is preferably 10.0%, more preferably 5.0%, and most preferably 1.0%.
[0110] La2O3 is an optional component that can improve the mechanical strength of glass-ceramics when its content exceeds 0%.
[0111] On the other hand, if the La2O3 content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the La2O3 content is preferably 3.0%, more preferably 2.0%, and most preferably 1.0%.
[0112] Y2O3 is an optional component that can improve the mechanical strength of glass-ceramics when its content exceeds 0%.
[0113] On the other hand, if the Y2O3 content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the Y2O3 content is preferably 3.0%, more preferably 2.0%, and most preferably 1.0%.
[0114] Nb2O5 is an optional component that can improve the mechanical strength of glass-ceramics when its content exceeds 0%.
[0115] On the other hand, if the Nb2O5 content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the Nb2O5 content is preferably 5.0%, more preferably 2.0%, and most preferably 1.0%.
[0116] Ta2O5 is an optional component that can improve the mechanical strength of glass when its content exceeds 0%.
[0117] On the other hand, if the Ta2O5 content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the Ta2O5 content is preferably 5.0%, more preferably 2.0%, and most preferably 1.0%.
[0118] WO3 is an optional component that can improve the mechanical strength of glass when its content exceeds 0%.
[0119] On the other hand, if the WO3 content is too high, the devitrification resistance can easily decrease. Therefore, the upper limit of the WO3 content is preferably 5.0%, more preferably 2.0%, and most preferably 1.0%.
[0120] In the microcrystalline glass of the present invention, the clarifying agent may also contain As2O3, Sb2O3, CeO2, and one or more selected from the group consisting of F, Cl, NOx, and Sox. However, the upper limit of the clarifying agent content is preferably 5.0%, more preferably 2.0%, and most preferably 1.0%.
[0121] Within the scope of not impairing the properties of the microcrystalline glass of this application, other components not mentioned above may be added to the microcrystalline glass of this invention as needed. However, in addition to Ti, Fe, Zr, Nb, W, La, Gd, Y, Yb, and Lu, even small amounts of various transition metal components such as V, Cr, Mn, Co, Ni, Cu, Ag, and Mo, either alone or in combination, can cause glass coloring and have the property of absorbing specific wavelengths within the visible range; therefore, it is preferable not to contain them in practice.
[0122] Furthermore, various components of Pb, Th, Cd, Tl, Os, Be, and Se have been identified as harmful chemical substances in recent years, leading to a trend towards controlling their application. Environmentally friendly measures are necessary not only for glass manufacturing processes but also for processing and post-production treatment. Therefore, when considering environmental impact, it is best to avoid products containing these components altogether.
[0123] In the microcrystalline glass of the present invention, the glass composition may consist only of the above-mentioned components, but other components may be added within a range that does not seriously impair the glass properties. For example, TeO2, Bi2O3, etc. may be added.
[0124] [Physical properties of glass-ceramics]
[0125] Preferably, the microcrystalline glass of the present invention has the following characteristics.
[0126] Preferably, the microcrystalline glass of the present invention has high devitrification resistance, and more specifically, has a low liquidus temperature. That is, the upper limit of the liquidus temperature of the glass of the present invention is preferably 1420°C, more preferably 1380°C, more preferably 1340°C, and most preferably 1300°C. Therefore, even when molten glass flows out at a lower temperature, devitrification during glass formation from the molten state can be reduced, and the impact on the substrate using the microcrystalline glass and its optical properties can also be reduced. Furthermore, since glass can be formed even at a lower melting temperature, deterioration of the platinum apparatus and mold can be suppressed, and energy consumption during glass forming can be reduced, thus lowering the production cost of the glass.
[0127] On the other hand, there is no particular limitation on the lower limit of the glass liquid phase temperature of the present invention. The lower limit of the liquid phase temperature of the glass prepared according to the present invention is preferably 1000°C, more preferably 1100°C, and even more preferably 1200°C.
[0128] Here, the liquidus temperature is an indicator of devitrification resistance. In this specification, the value determined by the following method will be used as the liquidus temperature. First, 30 cc of glass shards are placed into a 50 ml platinum crucible and held at 1500 °C until it is completely molten. Second, after cooling to the specified temperature and holding for 12 hours, the sample is removed from the furnace and cooled, and the glass surface and presence of crystals are observed. Observations are made in increments of 10 °C up to 1200 °C. Within this specified temperature range, the lowest temperature at which no crystals are visible is taken as the liquidus temperature.
[0129] The microcrystalline glass of the present invention has a molten glass viscosity of 10 dPa·s or higher at the liquidus temperature. Due to this viscosity, the formation of streaks can be suppressed, allowing for the forming of thin sheets from molten glass or by direct pressing. Therefore, the molten glass viscosity at the liquidus temperature of the glass of the present invention is preferably 10 dPa·s or higher, more preferably 100 dPa·s or higher, more preferably 350 dPa·s or higher, and most preferably 500 dPa·s or higher.
[0130] The viscosity of the molten glass in the microcrystalline glass of the present invention is preferably 1000 dPa·s or less at 1400°C. This viscosity helps to suppress the reduction of defoaming properties, the deterioration of glass production equipment caused by excessive temperature rise during clarification, the introduction of impurities, and the reduction coloring of the molten glass. Therefore, the viscosity of the molten glass in the glass of the present invention at 1400°C is preferably 1000 dPa·s or less, more preferably 800 dPa·s or less, more preferably 650 dPa·s or less, and most preferably 500 dPa·s or less.
[0131] The microcrystalline glass of the present invention preferably has a Vickers hardness [Hv] of 600 or higher. Due to this hardness, scratches can be suppressed, and mechanical strength can be improved. Therefore, the Vickers hardness [Hv] of the microcrystalline glass of the present invention is preferably 600 or higher, more preferably 650 or higher, more preferably 700 or higher, and most preferably 730 or higher.
[0132] The microcrystalline glass substrate of the present invention can be chemically strengthened by forming a compressive stress layer through ion exchange treatment. When forming the compressive stress layer, the compressive stress value of the compressive stress layer is preferably 300 MPa or more. Having such a compressive stress value can suppress crack propagation and improve mechanical strength. Therefore, when performing chemical strengthening, the compressive stress value of the compressive stress layer of the microcrystalline glass substrate of the present invention is preferably 300 MPa or more, more preferably 600 MPa or more, and most preferably 800 MPa or more.
[0133] The thickness of the compressive stress layer in the microcrystalline glass substrate of the present invention is preferably 1 μm or more. Because the compressive stress layer has such a thickness, even if deep cracks occur in the microcrystalline glass substrate, crack propagation or substrate fracture can be suppressed. Therefore, the thickness of the compressive stress layer is preferably 1 μm or more, more preferably 5 μm or more, and most preferably 8 μm or more.
[0134] The microcrystalline glass substrate of the present invention is preferably designed to withstand the impact of a 130g steel ball dropped from a height of 100cm without breaking. Due to this impact resistance, it can withstand the impact of drops or collisions when used as a protective component. Therefore, the drop height from which a 130g steel ball can be dropped without breaking is preferably 100cm, more preferably 150cm, and most preferably 180cm.
[0135] [Production Method]
[0136] The microcrystalline glass of the present invention can be manufactured, for example, by the following method: Raw materials are uniformly mixed to ensure that the various components are within a specified range; the resulting mixture is placed in a platinum or quartz crucible; and, depending on the melting ease of the glass composition, it is melted in an electric or gas furnace at a temperature range of 1300–1540°C for 5–24 hours. After stirring to ensure uniformity, the mixture is cooled to a suitable temperature and cast into a mold, then slowly cooled.
[0137] [Forming of raw glass]
[0138] The blank glass of the microcrystalline glass of the present invention can be melted and formed by well-known methods. Furthermore, the method for forming the glass melt is not limited.
[0139] Crystallization of raw glass
[0140] The blank glass of the microcrystalline glass of the present invention undergoes heat treatment after forming or forming processing to uniformly precipitate crystals inside the glass. This heat treatment can be performed in one stage, but preferably in two stages at different temperatures. That is, a nucleation process is first performed by heat treatment at a first temperature, and then a crystal growth process is performed by heat treatment at a second temperature higher than the nucleation process. The heat treatment performed at the first temperature is referred to as the first heat treatment, and the heat treatment performed at the second temperature is referred to as the second heat treatment.
[0141] Furthermore, by performing heat treatment at the temperature of the first stage, the nucleation and crystal growth processes can be carried out continuously. That is, the temperature is raised to a specified heat treatment temperature, and after reaching the heat treatment temperature, the temperature is held for a certain period of time, and then the temperature can be lowered.
[0142] To achieve the desired physical properties of the glass-ceramic, the preferred heat treatment conditions are as follows.
[0143] The first temperature is preferably 600℃~750℃. The first heat treatment can also be omitted. The second temperature is preferably 650℃~850℃.
[0144] The holding time at the first temperature is preferably 0 to 2000 minutes, and most preferably 180 to 1440 minutes.
[0145] The holding time at the second temperature is preferably 0 to 600 minutes, and most preferably 60 to 300 minutes.
[0146] When performing heat treatment at the temperature of stage 1, the heat treatment temperature is preferably in the range of 600°C to 800°C, and more preferably in the range of 630°C to 770°C in order to precipitate the desired crystalline phase. In addition, the holding time at the heat treatment temperature is preferably 0 minutes to 500 minutes, and more preferably 60 minutes to 300 minutes, in order to precipitate the desired crystalline phase.
[0147] In addition, the so-called "holding time of 0 minutes" means that the temperature starts to drop or rise again less than 1 minute after it is reached.
[0148] The glass or microcrystalline glass of the present invention can be used to manufacture glass-shaped bodies using methods such as grinding and polishing. That is, glass-shaped bodies can be manufactured by mechanical processing such as grinding and polishing of the glass or microcrystalline glass. By processing the glass-shaped body into a thin sheet shape, a microcrystalline glass substrate based on the microcrystalline glass of the present invention can be produced. Furthermore, the method of manufacturing the glass-shaped body is not limited to these methods.
[0149] In order to further improve the mechanical strength, the microcrystalline glass substrate of the present invention can form a compressive stress layer. In addition to improving mechanical properties through precipitation crystallization, the microcrystalline glass of the present invention can also achieve higher strength by forming a compressive stress layer.
[0150] Methods for forming a compressive stress layer include, for example, a chemical strengthening method that involves an exchange reaction between an alkaline component present on the surface of a glass-ceramic substrate and an alkaline component with a larger ionic radius, thereby forming a compressive stress layer on the surface. Other methods include a thermal strengthening method that involves heating the glass-ceramic substrate and then rapidly cooling it, and an ion implantation method that involves implanting ions into the surface of the glass-ceramic substrate.
[0151] Chemical strengthening can be implemented using the following process: The microcrystalline glass substrate is brought into contact with or immersed in molten salt containing potassium or sodium, such as potassium nitrate (KNO3), sodium nitrate (NaNO3), or a complex salt thereof, heated to 350–500°C for 0.1–12 hours. This process reduces the lithium content (Li) present in the glass phase near the surface. + (ion) or sodium component (Na) + Ions), and basic components with radii larger than these ions, namely sodium (Na). + (ion) or potassium component (K) + Ion exchange reactions occur, resulting in a compressive stress layer forming on the surface of the substrate.
[0152] By performing ion exchange through chemical strengthening, the microcrystalline glass of the present invention can form a compressive stress layer with a compressive stress value of 300 MPa or more and a thickness of 1 μm or more. According to a more preferred embodiment, a compressive stress layer with a compressive stress value of 600 MPa or more can be formed; according to the most preferred embodiment, a compressive stress layer with a compressive stress value of 800 MPa or more can also be formed. Furthermore, according to a more preferred embodiment, a compressive stress layer with a thickness of 5 μm or more can be formed; according to the most preferred embodiment, a compressive stress layer with a thickness of 8 μm or more can also be formed.
[0153] The thermal strengthening method is not particularly limited. For example, after heating the microcrystalline glass substrate to 300°C to 600°C, rapid cooling such as water cooling and / or air cooling can be performed, and a compressive stress layer can be formed based on the temperature difference between the surface and the interior of the glass substrate. In addition, the compressive stress layer can be formed more effectively by combining it with the above-mentioned chemical treatment method.
[0154]
Example
[0155] The microcrystalline glass and substrate of embodiments of the present invention are recorded in a table. The microcrystalline glass of embodiments of the present invention is manufactured as described below. First, as raw materials for various components, corresponding oxides, hydroxides, carbonates, nitrates, fluorides, chlorides, hydroxides, and metaphosphate compounds are selected, and these raw materials are weighed according to the composition ratios shown in the table for each embodiment, and then mixed uniformly. Next, the mixed raw materials are placed in a platinum crucible and melted in an electric furnace at a temperature range of 1300-1550°C for 5-24 hours, depending on the melting difficulty of the glass composition. Then, the molten glass is stirred to make it uniform and cast into a mold or the like, and slowly cooled to obtain a blank glass.
[0156] For the obtained raw glass, a one-stage or two-stage heat treatment is performed to manufacture glass-ceramics in order to perform nucleation and crystallization. A one-stage heat treatment was performed in Examples 1 to 3 and 36 to 38, and a two-stage heat treatment was performed in other examples. In the table, the conditions for the first-stage heat treatment are recorded in the "Nucleation Conditions" column, and the conditions for the second-stage heat treatment are recorded in the "Crystallization Conditions" column. The temperatures of the heat treatment and the holding times at those temperatures are as described in the table.
[0157] The manufactured microcrystalline glass is cut and ground to form a shape with a 40mm angle and a thickness of more than 1mm. The opposite surfaces are then polished in parallel to achieve a thickness of 1mm, thus obtaining a microcrystalline glass substrate.
[0158] Here, for the embodiment described in the "Chemical Strengthening Conditions" section, chemical strengthening is performed by immersing the microcrystalline glass, after parallel polishing of the opposing surfaces, in molten KNO3 salt to obtain a microcrystalline glass substrate. The immersion temperature and immersion time in the molten salt are as described in the "Chemical Strengthening Conditions" section of the table.
[0159] The visible light transmittance of the microcrystalline glass in this embodiment was measured using a Hitachi U-4000 spectrophotometer. The transmittance at 240–800 nm was determined for a 1 mm thick microcrystalline glass with parallel polishing of its opposing surfaces. The transmittance at 410 nm, 500 nm, and 700 nm was then calculated. Transmittance includes surface reflection loss. In the table, the difference between the transmittance at 700 nm and 500 nm is recorded in the "ΔT1(700, 500)" column, and the difference between the transmittance at 700 nm and 410 nm is recorded in the "ΔT2(700, 410)" column.
[0160] The compressive stress value and the thickness of the compressive stress layer on the surface of the chemically strengthened microcrystalline glass substrate were measured using a glass surface stress meter FSM-6000LE manufactured by Orihara Corporation. The measurement conditions were calculated with the sample's refractive index of 1.54 and optical elastic constant of 28.8 [(nm / cm) / MPa].
[0161] Additionally, the Vickers hardness of the microcrystalline glass substrate in the embodiment is calculated by dividing the load (N) when a diamond pyramidal indenter with a 136° face angle is pressed into a pyramid-shaped indentation on the test surface by the surface area (mm) calculated through the length of the indentation. 2 The value is expressed as (). Using an Akashi Microhardness Tester MVK-E manufactured by Akashi Corporation, the test was conducted with a load of 9.80 (N) and a holding time of 15 (seconds). Furthermore, for the examples described in the "Chemical Strengthening Conditions" section, the test was performed on a chemically strengthened substrate.
[0162] In the embodiments, the crystal phase of the microcrystalline glass before chemical strengthening was identified using an X-ray diffraction analysis device (Philips X'PERT-MPD) by the angle of the peaks displayed on the X-ray diffraction pattern, and as needed using TEMEDX (JEM2100F, Nippon Electronics).
[0163] In this embodiment, the "liquid phase temperature" of the microcrystalline glass was determined by placing 30cc of glass-like shards into a 50ml platinum crucible and molten it completely at 1500°C. The temperature was then lowered to a specified temperature and maintained for 12 hours. After cooling outside the furnace, the glass surface and any crystallization were observed to determine the lowest temperature at which no crystallization was observed. The specified cooling temperature was implemented in 10°C increments up to 1200°C.
[0164] The viscosity of the molten glass was measured using a falling ball viscometer (manufactured by OPT Corporation) to obtain the viscosity at the liquidus temperature and at 1400°C.
[0165] For the examples involving drop ball testing, values were recorded in the "Drop Ball Test Height" column. The drop ball test height represents the maximum impact a substrate with a 40mm angle × 1.3mm thickness, polished on both surfaces, can withstand being dropped from a specified height onto a rubber sheet without breaking. Specifically, the test was conducted starting at a drop height of 100cm, and then at varying heights of 150cm and 180cm without breakage. Furthermore, for the examples described in the "Chemical Strengthening Conditions" column, chemically strengthened substrates were used as the test subjects.
[0166] Furthermore, the test recorded in the embodiment as 180cm indicates that the steel ball withstood the impact without breaking even when dropped from a height of 180cm, suggesting that it may not break even at heights above that.
[0167] Table 1
[0168]
[0169] Table 2
[0170]
[0171] Table 3
[0172]
[0173] Table 4
[0174]
[0175] Table 5
[0176]
[0177] Table 6
[0178]
[0179] Table 7
[0180]
[0181] Table 8
[0182]
[0183] As shown in the table, the microcrystalline glass of the embodiments of the present invention can achieve the desired transmittance and color balance.
[0184] Therefore, the microcrystalline glass of the embodiments of the present invention, with a thickness of 1 mm, exhibits a light transmittance exceeding 85% at a wavelength of 500 nm. Furthermore, with a thickness of 1 mm, the difference between the light transmittance at a wavelength of 700 nm and that at 500 nm is within 1.5%. Additionally, the difference between the light transmittance at a wavelength of 700 nm and that at a wavelength of 410 nm is within 5.0%. Thus, it can be demonstrated that the microcrystalline glass of the embodiments of the present invention exhibits good visible light transmittance and color balance.
[0185] In addition, the microcrystalline glass of the present invention exhibits good resistance to devitrification, as well as good meltability and formability during melting, and can also obtain the desired crystalline phase.
[0186] It can be shown that the substrate of the present invention, even if it is a microcrystalline glass, can obtain high compressive stress through chemical strengthening, and a deep compressive stress layer can be formed in a short time.
[0187] Therefore, it can be shown that the microcrystalline glass and substrate of the embodiments of the present invention have the desired translucency and color balance, and also have high mechanical strength.
[0188] The present invention has been described in detail above with reference to examples. However, the purpose of this embodiment is merely to illustrate the invention. It should be understood that those skilled in the art can make various modifications without departing from the spirit and scope of the invention.
Claims
1. A microcrystalline glass, characterized in that, Calculated in mole percent of oxides, The SiO2 content is 30.0%–70.0%. The content of Al2O3 is 8.0% to 25.0%. The Na2O content is greater than 0% and less than 25.0%. The MgO content ranges from 0% to 25.0%. The ZnO content ranges from 0% to 30.0%, and The TiO2 content is 0%–10.0%. The content of B2O3 is less than 2.0%. The molar ratio [Al₂O₃ / (MgO+ZnO)] is between 0.5 and 2.
0. The molar ratio [TiO2 / Na2O] is between 0 and 0.
41. The crystal phases contain MgAl2O4, Zn2SiO4, and Zn2Al4Si5O4. 18 and Mg2Al4Si5O 18 Choose one or more from the options. The transmittance at a wavelength of 500nm, including reflection loss, is over 88.6% within a 1mm thickness.
2. The microcrystalline glass according to claim 1, characterized in that, Calculated in molar percentage of oxides, the molar ratio of MgO to Na2O [MgO / Na2O] is between 0 and 1.
60.
3. The microcrystalline glass according to claim 1 or 2, characterized in that, Within a 1mm thickness, the difference between the transmittance at wavelength 700nm and the transmittance at wavelength 500nm, including reflection loss, is within 2.0%, and the difference between the transmittance at wavelength 700nm and the transmittance at wavelength 410nm is within 6.0%.
4. The microcrystalline glass according to claim 1 or 2, characterized in that, Calculated in mole percent of oxides, the combined content of MgO and ZnO is between 1.0% and 30.0%.
5. The microcrystalline glass according to claim 1 or 2, characterized in that, Calculated in mole percent of oxides, The content of P2O5 is 0%–10.0%. The K2O content ranges from 0% to 20.0%. The CaO content is 0%–10.0%. The content of BaO is 0% to 10.0%. The FeO content is 0%–8%. The ZrO2 content is 0%–10.0%. The SnO2 content is 0% to 5.0%.
6. The microcrystalline glass according to claim 1 or 2, characterized in that, Calculated in mole percent of oxides, The content of Li2O is 0% to 10.0%. The content of SrO is 0% to 10.0%. The content of La2O3 is 0% to 3%. The content of Y2O3 is 0% to 3%. The Nb2O5 content is 0%–5%. The content of Ta2O5 is 0% to 5%. The content of WO3 is 0% to 5%.
7. A microcrystalline glass substrate, comprising the microcrystalline glass according to claims 1 to 6 as a substrate, having a compressive stress layer on its surface, characterized in that, The compressive stress value of the compressive stress layer is above 300 MPa.
8. The microcrystalline glass substrate according to claim 7, characterized in that, The thickness of the compressive stress layer is 1 μm or more.
Citation Information
Patent Citations
Crystallized glass and crystallized glass substrate for information recording medium
JP2014114200A
Crystallized glass substrate for information recording medium and method of producing the same
CN101905952A
Methods to texture opaque, colored and translucent materials
CN105164078A
Microcrystalline glass, microcrystalline glass product and manufacturing method thereof
CN111807705A
Crystallized glass and its production
JP1997263424A
